Correlations of serum 25-hydroxy-vitamin D, CD4+ CD25+ CD127– regulatory T cells and total immunoglobulin E in children with recurrent respiratory tract infections.: Las correlaciones séricas de 25-hidroxivitamina D, CD4+ CD25+ CD127– linfocitos T reguladores e inmunoglobulina E total en niños con infecciones recurrentes del tracto respiratorio. - Yang, Yanfei; Fan, Na; Liu, Xingzhu; Wang, Lin; Wang, Zhihai; Hou, Yao; Wang, Ting; Wu, Yuqin (Investigación Clínica, 2024)
Recurrent respiratory tract infections (RRTIs) have a complex pathogenic mechanism. There may be correlations between expression levels of serum 25-hydroxy-vitamin D (25-OH-D), regulatory T cells (Tregs), total immunoglobulin E (IgE) and RRTIs. We aimed to explore the correlations of serum 25-OH-D, cluster of differentiation 4 (CD4)+ CD25+ CD127- Tregs and total IgE in children with RRTIs. A total of 150 children with pneumonia were enrolled as the subjects and randomly assigned into a control group (97 children with non- RRTIs) and an observation group (53 children with RRTIs). The expression levels of serum 25-OH-D, CD4+ CD25+ CD127- Tregs and total IgE were compared in RRTI children with different genders, stages, sites of lesions and severities of illness. The correlation was tested by Pearson analysis. The expression level of serum 25-OH-D was significantly higher in children with RRTIs in the upper respiratory tract than that in the lower respiratory tract, whereas the expression level of total IgE was significantly lower in children with RRTIs in the upper respiratory tract (p<0.05). The expression level of 25-OH-D was negatively correlated with expression levels of CD4+ CD25+ CD127- Tregs and total IgE (r=-0.355,-0.314, p<0.05), while a positive correlation was found between expression levels of CD4+ CD25+ CD127- Treg and total IgE (r=0.237, p<0.05). The area under the curve of combination of 25-OH-D, CD4+ CD25+ CD127- Treg and total IgE expression levels for predicting RRTIs was 0.852. The combined detection of the three indicators is conducive to enhancing the detection rate of RRTIs.